Corporate Commitment of Environment: Evidence from Sustainability Reports of Mining Companies in Indonesia - Kurnia Ekasari; Nurafni Eltivia; Andi Kusuma Indrawan; Apit Miharso (Indonesian Journal of Sustainability Accounting and Management, 2021)
This research aims to explore the commitment of Indonesian mining companies to environmental sustainability and ensure that they operate following ethical rules without damaging the nature. A content analysis investigates information related to the environment. Research sources include 33 environmental items seen from 7 sustainability reports of Indonesian mining companies. The text’s substance is also examined by identifying various specific characteristics of a message objectively, systematically, and in general. Research results showed that out of 45 mining companies in Indonesia, only 7 had disclosed sustainability reporting. All companies had an environmental commitment but with different stressing. Some companies reveal more about biodiversity; some are more focused on managing both renewable and nonrenewable energy, while others concentrate on effluents and waste. Since mining companies use numerous natural resources as their raw material, these companies should be more committed and concerned about the sustainability of nature and the environmental damage it causes. This study only examined seven sustainability reports from Indonesian mining companies. For future research, the researcher suggested observing annual reports of mining companies that do not disclose sustainability reporting and expressed concerns about the environment, both in Indonesia and Asia as a whole.